The Bundi Gīta-Govinda - Vatsyayan, Kapila (Bharat Kala Bhavan, 1981)
Text and notes on paintings on the theme of Jayadeva's Gītagovinda, Sanskrit lyric on Rādhā and Krishna, Hindu deities, presenting the Bundi school in Indic painting; from the collection of the Bharat Kala Bhavan.